Sex Differences In Cooperation: A Meta-analytic Review of Social Dilemmas - BALLIET, D. (Institutional Knowledge at Singapore Management University, 2010)
We examine predictions of evolutionary psychology and sociocultural theories of sex differences in cooperation using a meta-analysis of 85 studies from the literature on social dilemmas. The sociocultural prediction that women are generally more cooperative than men does not find support, and the overall effect size is not statistically different from zero. However, supporting evolutionary theory, male-male interactions are more cooperative than female-female interactions and men become more cooperative than women after several iterations of a social dilemma. As predicted by the sociocultural perspective, women are more cooperative than men in mixed-sex interactions. However, failing to support the sociocultural perspective, women are slightly more cooperative than men in larger groups. We discuss the results in the context of each theoretical perspective, address the need for an integrated biological and cultural approach to sex differences in cooperation, and outline directions for future research.